Do Chief Audit Executives Able to Influence Real Earnings Management Practices? Evidence from Indonesia - Taufiq Taufiq (Accounting Analysis Journal, 2023)
Purpose : This study aims to investigate the relationship between financial expertise and tenure of the Chief Audit Executive [CAE] on real earnings management [REM] practices Method : This study uses a sample of 797 observations from companies in the manufacturing sector in Indonesia during the period 2012 – 2019. For data analysis, regression of feasible generalized least squares was used. Data related to financial expertise and tenure of CAE were manually collected from the annual report and financial data was obtained from Thomson-Reuters Database. Findings : The results of this study indicate that CAE with better financial expertise is associated with lower REM. Conversely, this study also indicates that CAE tenure has an association with higher REM. This result is robust by using an alternative REM measurement. By breaking down the indicators of CAE’s financial expertise, namely CAE’s certification, experience in financial positions within/inside the company or outside the company, the results show that CAE certification has the largest effect on REM. Novelty : This study contributes to the real earnings management and internal audit literature by demonstrating the importance of attributes possessed by CAEs as leaders of the internal audit function in mitigating REM practices. Keywords : Chief Audit Executive, Financial Expertise, Tenure, Real Earnings Management